Psychosocial Issues in Breast Cancer Patients Undergoing Chemotherapy: A Literature Riview - Yori Yolanda; Titin Indriati; Riza Arisanty Latifah (GLOBAL HEALTH SCIENCE GROUP, 2026)
One of the most frequently Identified side effects of chemotherapy in breast cancer patients is psychosocial issues. This scientific review is which conducted through a literature review is aim at identifying psychosocial issues experienced by breast cancer patients undergoing chemotherapy. Articles were searched through several sources, including Google Scholar and PubMed, covering publications from 2020 to 2025. A total 861 articles were initially found, from which 10 articles were selected for analysis based in the inclusion criteria. The inclusion criteria selected with the keywords Breast cancer patients, chemotherapy, and psychosocial problems. The strategy used by researchers in searching and selecting the articles is the PICO framework. The results of the literature review indicated that several psychosocial issues faced by the breast cancer patients are including anxiety, body image disturbances, sleep pattern disorders, and depression. Early identification of emotional conflict and psychosocial issues in breast cancer patients is needed, along with several psychosocial interventions to reduce of level these psychosocial issues.